1996
DOI: 10.1111/j.1432-1033.1996.0320r.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Fine Saccharide‐Binding Specificity of Dioclea grandiflora Lectin and Concanavalin A

Abstract: The lectin from the seeds of Dioclea grandifora (DGL) is a Man/Glc-specific tetrameric protein with physical and saccharide-binding properties reported to be similar to that of the jack bean lectin concanavalin A (ConA). Unlike other plant lectins, both DGL and ConA bind with high affinity to the core trimannoside moiety, 3,6-di-O-(a-~-mannopyranosyl)-a-~-mannopyranoside, which is present in all asparagine-linked carbohydrates. In the present study, hemagglutination inhibition techniques have been used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
40
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 32 publications
7
40
0
Order By: Relevance
“…The precipitation reactions were inhibited by the presence of Me-␣Man or dissolved upon addition of the monosaccharide. Thus, the multivalent binding activities of the sugars were confirmed, since tetrameric ConA (12) and tetrameric DGL (33) are known to precipitate with multivalent carbohydrates and glycoproteins. ITC measurements, however, require the presence of soluble complexes during the titration experiment (ϳ1-2 h), and thus conditions in which the sugar complexes with ConA and DGL remained soluble were investigated.…”
Section: Resultsmentioning
confidence: 73%
“…The precipitation reactions were inhibited by the presence of Me-␣Man or dissolved upon addition of the monosaccharide. Thus, the multivalent binding activities of the sugars were confirmed, since tetrameric ConA (12) and tetrameric DGL (33) are known to precipitate with multivalent carbohydrates and glycoproteins. ITC measurements, however, require the presence of soluble complexes during the titration experiment (ϳ1-2 h), and thus conditions in which the sugar complexes with ConA and DGL remained soluble were investigated.…”
Section: Resultsmentioning
confidence: 73%
“…These lectins differ in their binding specificities for complex type carbohydrates (Gupta et al 1996, Dam et al 1998. In addition, they show distinct pHdependent dimer-tetramer equilibrium (Grangeiro et al 1997, Calvete et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The many biochemical, biophysical, and structural studies carried out on ConA, both for the native and ConA-saccharide complexes (Reeke and Becker, 1988;Sharon and Lis, 1990;Naismith et al, 1994;Emmerich et al, 1995;Bouckaert et al, 1995;Naismith and Field, 1996;Harrop et al, 1996;Kanellopoulos et al, 1996a, b;Parkin et al, 1996;Hamodrakas et al, 1997;and cited references), make this protein the best characterized plant lectin and an extensively studied representative of its protein family. However, the lectins from Canavalia ensiformis and Dioclea grandijZora display different fine-saccharide-binding specificity for C-glycosides (Weatherman et al, 1996) and complex carbohydrates (Gupta et al, 1996). In addition, studies from our laboratories indicated that lectins isolated from taxonomically closely related legume plants exert distinct biological activities.…”
mentioning
confidence: 93%